The memoir of John Butter : surgeon, militiaman, sportsman and founder of the Plymouth Royal Eye Infirmary - Tracy, Dee; Tracy, Mike (Devon and Cornwall Record Society (Series), 2023)
John Butter's Memoir is a first-hand account of nineteenth-century medicine, by a pioneering physician and surgeon who founded one of Britain's earliest eye hospitals. It is published here for the first time.